PENGARUH HARGA, BRAND IMAGE,DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Gracia Skin Clinic Semarang) - Fildzah Hanifati; Handoyo Djoko Waloejo (Universitas Diponegoro, 2019)
The lifestyle of women at this time demands to pay more attention to appearance, for that skin care is very important for everyone. Moreover, to overcome various complaints that cause problems on the skin that can reduce beauty, then everyone needs the right product and care. The clinical need for beauty in the community, makes the beauty business grow rapidly and compete with each other. One of the beauty clinics that still survive today is Gracia clinic Semarang. This study aims to determine the effect of prices, image brands and service quality on purchasing decisions. The type of research used is explanatory research and the sampling technique uses non probability sampling techniques with purposive sampling method, the technique of collecting data using a questionnaire. The number of samples used in this study were 100 respondents in the city of Semarang. This research uses quantitative and qualitative analysis with validity test, reliability test, correlation coefficient, coefficient of determination, simple and multiple regression tests, significance of t test, and F test with SPSS for windows version 16.0. The results of this study indicate that the price variable, brand image and service quality have a strong and positive influence on Gracia Skin Clinic purchasing decisions. Service quality and price variables show 0.651 that the relationship between the two variables to purchasing decisions has a strong relationship. The price variable in the determination test (R square) shows that 45.7% affects purchasing decisions so 54.3% is influenced by other factors. Brand image variable in the determination test (R square) shows that 44.2% influences purchasing decisions so 55.8% is influenced by other factors. The service quality variable in the determination test (R square) shows that 87.6% influence purchasing decisions so that 12.4% is influenced by other factors.